ECOGENLit: Economics literature on plant and livestock genetic resources - Zambrano, Patricia; Smale, Melinda; Drucker, A.; Álvare, Luz Marina; Yerramareddy, Indira (2005)
On October 23-25, 2003, Bioversity International convened a workshop for the System-wide Genetic Resources Programme (SGRP) of the CGIAR about ”Managing Agricultural Biodiversity for Sustainable Development,” hosted by the World Agroforestry Centre (ICRAF) in Nairobi, Kenya. As an outcome of that workshop, SGRP commissioned a paper assessing the status of valuation methods for crop and livestock components of agricultural biodiversity, with particular emphasis on developing agricultural economies, and a thematic bibliography of related literature. The commissioned paper is now a chapter book: Smale, M., and A. G. Drucker. In press. Managing crop and livestock biodiversity in developing economies: a review of the economics literature. In A. Kontoleon, U. Pascual, and T. Swanson (eds). Frontiers of biodiversity economics. Cambridge, UK: Cambridge University Press. The associated thematic literature is Economics Literature on Plant and Livestock Genetic Resources(ECOGENLit). ECOGENLit is a unique collection of literature that reflects the emerging interest of applied economists in plant and livestock biodiversity. The web-based bibliography is organized by themes and is also a complete searchable database. The collection is updated on a yearly basis and the goal is to gather all economics literature in the area. To attain this goal ECOGENLit welcomes paper submissions from researchers and interested parties. All relevant papers will be included in the yearly updates. Note that ECOGENLit in some cases provides active links to download the article abstract or the full text from the publisher's site. Access to the abstract or the full text of these publications requires Internet connection. Browsing some of these full text publications may require Adobe Acrobat Reader software to be installed on your computer. If you do not already have this program, you may download and install from the Adobe Acrobat Reader